2021
DOI: 10.1091/mbc.e21-04-0178
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Nst1 is a novel component of P-bodies and is a specific suppressor of proteasome base assembly defects

Abstract: Proteasome assembly utilizes multiple dedicated assembly chaperones and is regulated by signaling pathways that respond to diverse stress conditions. To discover new factors influencing proteasome base assembly, we screened a tiled high-copy yeast genomic library to identify dosage suppressors of a temperature-sensitive proteasome regulatory particle (RP) base mutant. The screen identified Nst1, a protein that when overexpressed, specifically suppressed the temperature sensitivity and proteasome-assembly defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Throughout different stages of RP assembly, RP chaperones act by the same mechanism—binding to their cognate proteasomal ATPases. The chaperones may be able to satisfy different requirements for the accuracy of a given assembly event via acting with Not4 and other proteins as potential checkpoint factors ( Cheng et al, 2021 ; Zavodszky et al, 2021 ), thereby providing the first point of quality control for the proteasome holoenzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout different stages of RP assembly, RP chaperones act by the same mechanism—binding to their cognate proteasomal ATPases. The chaperones may be able to satisfy different requirements for the accuracy of a given assembly event via acting with Not4 and other proteins as potential checkpoint factors ( Cheng et al, 2021 ; Zavodszky et al, 2021 ), thereby providing the first point of quality control for the proteasome holoenzyme.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the function of Nst1 in PB accumulation because we observed that the antiproliferative phenotype of its overexpression was suppressed by well-known components of PBs, such as Psp2 and Pop2 ( Supplementary Figure S1 ). Although we are studying the function of Nst1 in PB formation, another group has recently reported it as a novel PB component [ 29 ]. When we recognized that the endogenous EGFP-tagged Nst1 is strongly self-condensed and co-localized with the Dcp2 and Edc3 condensates in the post-exponential growth phases, we expected that the endogenous EGFP-tagged Nst1 in exponentially growing cells would be observed as puncta similar to those of cells exposed to glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Because both processes of PB accumulation from small to large bodies are not discrete but continuous, it is challenging to determine the degree of PB accumulation. In previous studies, PB accumulation was quantified by the number of cells containing intensified puncta [29]. Instead, to accurately measure the extent of accumulation during the process, we applied a systematic quantification method by image processing utilizing FIJI ImageJ (https://imagej.net/software/fiji/, accessed on 7 January 2022) with the BaSiC plugin [30].…”
Section: Overexpressed Nst1 Drives the Condensation Of Pb Components ...mentioning
confidence: 99%